Votes, drugs, and violence: the political logic of criminal wars in Mexico - Trejo, Guillermo (Cambridge studies in comparative politics, 2020)
"In the most widely-accepted minimalist definition, democracy is conceived as a governance system in which citizens select their representatives through competitive elections and resolve their differences without bloodshed. While in recent decades scholars have shown that countries transitioning from authoritarian rule to democracy tend to experience major outbreaks of political violence, and that peace prevails only after democratic rules and practices have been fully engrained in society, the association of democratic mechanisms with different forms of violence continues to be mind-boggling. It continues to be analytically surprising and morally disheartening when newly established democratic mechanisms like voting and competitive elections become catalysts of collective violence. It is even more disconcerting when democratic mechanisms become triggers of violent conflict among "non-political" actors like organized criminal groups and drug cartels, which have long been considered quintessential examples of private illicit actors with no interest or meaningful connection with electoral politics. This book is the result of a long intellectual shared journey aimed at making sense of an uncommonly intense wave of large-scale criminal violence in Mexico that began six years after the end of one-party rule, when President Felipe Calderón (2006-2012) declared war on the country's drug cartels, triggering multiple state-cartel and inter-cartel violent conflicts across Mexican territory"--